2020
DOI: 10.1093/ageing/afaa260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 lockdown on disease recognition and utilisation of healthcare services in the older population in Germany: a cross-sectional study

Abstract: Background There is little evidence about the utilization of healthcare services and disease recognition in the older population, which was urged to self-isolate during the COVID-19 lockdowns. Objectives We aimed to describe the utilization of physician consultations, specialist referrals, hospital admissions, and the recognition of incident diseases in Germany for this age group during the COVID-19 lockdown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 18 publications
5
72
0
17
Order By: Relevance
“…Our results extend previous research that was done in Germany based on medical record data of older adults [11]. This previous study showed that GP consultations and referrals to hospital specialist outpatient care decreased substantially (up to -39%) during the lockdown in the first wave of the pandemic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results extend previous research that was done in Germany based on medical record data of older adults [11]. This previous study showed that GP consultations and referrals to hospital specialist outpatient care decreased substantially (up to -39%) during the lockdown in the first wave of the pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Very few studies were undertaken in older populations. One study from Germany used healthcare registration data of older adults, and observed a decrease in healthcare use and diagnosis of diseases during the lockdown period, compared to the same period 1 year earlier [11]. Another study among older adults > 75 years in the UK revealed no major problems with access to healthcare services during the first months of the COVID-19 pandemic [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent German study with 1,095 GPs and patients aged 65 or older found that there was a 14% decrease in consultations in May 2020 compared with the same time in 2019, and the rate of diabetes, dementia, depression, cancer and stroke diagnoses decreased during this period (between −17% and −26%). 28 In a survey of Australian GPs, 73% of practices had a reduction in bookings and 77% had a decrease in practice income; meanwhile, telephone calls (93%) and practice costs (81%) increased. 17 These results support our survey’s findings that these challenges have also been experienced by GPs in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been found that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany (8). Finally, this database has already been used for other studies investigating the impact of the Covid-19 pandemic on the healthcare system (9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%